Impact of Board Characteristics and Ownership Structure on NonPerforming Loan in Nepalese Commercial Banks - Aryal, Sagar Babu; Gupta, Saloni; Giri, Sapna; Rokaya, Shyam Bahadur; Mahato, Srijana; Pradhan, Sumit (Nepalese Journal of Finance, 2024)
This study examines the impact of board characteristics and ownership structure on non-performing loan of Nepalese commercial banks. The selected dependent variables are non-performing loan and credit to deposit ratio. Similarly, the selected independent variables are board size, board diversity, board independence, institutional ownership, audit committee and board meeting. The study is based on secondary data of 15 commercial banks with 105 observations for the period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of board characteristics and ownership structure on non-performing loan of Nepalese commercial banks. The study showed that board size has a positive impact on non-performing loan and credit-to-deposit ratio. It means that increase in board size leads to increase in non-performing loans and credit-to-deposit ratio. Similarly, board diversity has a positive impact on non-performing loan and credit-to-deposit ratio. It means that greater the proportion of female director in the board, higher would be the non-performing loan and credit-to-deposit ratio. Likewise, Furthermore, board independence director has a negative impact on non-performing loan. It indicates that increase in the numbers of independent director leads to decrease in non-performing loans. In addition, audit committee has a negative impact on non-performing loan. It indicates that larger the audit committee size, lower would be the non-performing loan. Furthermore, institutional ownership has a positive impact on non-performing loan. It shows that increase in the proportion of institutional ownership leads to increase in non-performing loan.